Incubadora universitária de empreendimentos de economia solidária: perspectivas de gestão de um sistema não hierarquizado e suas relações com o sistema burocrático - Morais, Cláudio Antonio (2018)
The objective of this research was to capture the ways of perceiving and understanding what the meaning of self-management is for the members of the nucleus researched, first in a broader perspective on the concept of self-management, later on by a search for an understanding of self- later understand the possible relationships derived within this insertion in a hierarchical institution. It is presented in the theoretical framework a look at bureaucracy, heterogeneity and self - management, aiming to analyze the insertion of incubator management in the field of Solidarity Economy, which work with the assumption of self - management, and this institutional relationship with the universities that belong to, and understood here as bureaucratic organizations. This is a Single Case Study done in an Integrated Multidisciplinary Nucleus of Studies, Training and Intervention in Solidarity Economy, belonging to a federal public university located in the interior of the State of São Paulo.